Inter-Firms Relationships and Supply Chain Strategy Mechanism in Indonesian Family SMEs - Kussudyarsana Kussudyarsana; Muhammad Halim Maimun; Anton Agus Setyawan; Ram Vemuri (International Journal of Supply Chain Management, 2020)
Abstract— In an emerging economy such as Indonesia, family firms represent the most common form of business organization. This study discussed the supply chain strategy mechanism for inter-firms relationships in context of family small medium enterprises (SMEs). This study investigated in what situation family SMEs should apply relational or and formal supply chain strategy mechanism. This study used multiple regression analysis to examine hypothesis. In the data collection, questionnaires were distributed to 350 owners and managers of small-medium enterprises, around seven cities in Java Island in Indonesia. Results indicated  two factors asset specificity and uncertainty – influenced both formal and relational supply chain strategy. Through the investigation of supply chain strategy mechanism in family SMEs this study contributes to answer the appropriateness of the application supply chain strategy mechanism in Family SME